Na(+)-d-glucose Cotransporter SGLT1 is Pivotal for Intestinal Glucose Absorption and Glucose-Dependent Incretin Secretion - Gorboulev, Valentin (American Diabetes Association, 2012)
To clarify the physiological role of Na(+)-d-glucose cotransporter SGLT1 in small intestine and kidney, Sglt1(−/−) mice were generated and characterized phenotypically. After gavage of d-glucose, small intestinal glucose absorption across the brush-border membrane (BBM) via SGLT1 and GLUT2 were analyzed. Glucose-induced secretion of insulinotropic hormone (GIP) and glucagon-like peptide 1 (GLP-1) in wild-type and Sglt1(−/−) mice were compared. The impact of SGLT1 on renal glucose handling was investigated by micropuncture studies. It was observed that Sglt1(−/−) mice developed a glucose-galactose malabsorption syndrome but thrive normally when fed a glucose-galactose–free diet. In wild-type mice, passage of d-glucose across the intestinal BBM was predominantly mediated by SGLT1, independent the glucose load. High glucose concentrations increased the amounts of SGLT1 and GLUT2 in the BBM, and SGLT1 was required for upregulation of GLUT2. SGLT1 was located in luminal membranes of cells immunopositive for GIP and GLP-1, and Sglt1(−/−) mice exhibited reduced glucose-triggered GIP and GLP-1 levels. In the kidney, SGLT1 reabsorbed ∼3% of the filtered glucose under normoglycemic conditions. The data indicate that SGLT1 is 1) pivotal for intestinal mass absorption of d-glucose, 2) triggers the glucose-induced secretion of GIP and GLP-1, and 3) triggers the upregulation of GLUT2.